Особенности течения хронического неатрофического гастрита у водителей дальних рейсов = Features of chronic non-atrophic gastritis in long-haul drivers - Anatoliy A. Avramenko; Rimma N. Korolenko; Sergey N. Smolyakov (Kazimierz Wielki University, 2015)
Avramenko А А, Korolenko R N, Smolyakov S N. Особенности течения хронического  неатрофического  гастрита у водителей дальних рейсов = Features of chronic non-atrophic gastritis in long-haul drivers. Journal of Education, Health and Sport. 2015;5(2):79-86. ISSN 2391-8306. DOI: 10.5281/zenodo.15572 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%282%29%3A79-86 https://pbn.nauka.gov.pl/works/540056 http://dx.doi.org/10.5281/zenodo.15572 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.10.2014. Revised 18.01.2015. Accepted: 25.01.2015.   УДК  616.33-002-072:616.33-002.44    ОСОБЕННОСТИ ТЕЧЕНИЯ ХРОНИЧЕСКОГО  НЕАТРОФИЧЕСКОГО  ГАСТРИТА У ВОДИТЕЛЕЙ ДАЛЬНИХ РЕЙСОВ FEATURES OF CHRONIC NON-ATROPHIC GASTRITIS IN LONG-HAUL DRIVERS   А.А. Авраменко *, Р.Н. Короленко **, С.Н. Смоляков *** АА Avramenko, RN KOROLENKO, SN Smolyakov   Кафедра биологии человека и животных Николаевского национального университета им. В.А. Сухомлинского*, Центр прогрессивной медицины и реабилитации «Rea+Med», г. Николаев*; Отделение функциональной диагностики 4-ой горбольницы, г. Николаев** Областной онкологический диспансер, г. Николаев***   Abstract        Was carried out comparative characteristics of these comprehensive survey of two groups of patients with chronic non-atrophic gastritis: Group 1 - 23 people in the profession "truck drivers" (freight), Group 2 - 26 people whose work is not connected with the movement of long distance. It was found that patients first non-atrophic gastritis chronic group proceeded significantly (p <0.05) with a higher degree of colonization of the gastric mucosa of H. pylori infection, 41.1% more cases were identified duodenal ulcer and 40.1 % more cases were identified gallbladder dyskinesia hypokinetic type of hypotonic compared with similar data obtained in patients in group 2.   Key words: chronic non-atrophic gastritis, duodenal ulcer, gallbladder dyskinesia.   Резюме ОСОБЛИВОСТІ   ПЕРЕБІГУ   ХРОНІЧНОГО НЕАТРОФІЧНОГО ГАСТРИТУ У ВОДІЇВ ДАЛЕКИХ РЕЙСІВ. Була проведена порівняльна характеристика даних комплексного обстеження двох груп пацієнтів з хронічним неатрофічним гастритом: 1-а група - 23 особи за професією «водій далеких рейсів» (перевезення вантажів), 2-а група - 26 осіб, робота яких не пов'язана з переміщенням на далекі відстані. Було з'ясовано, що у пацієнтів 1-ої групи хронічний неатрофічний гастрит протікав достовірно (р <0,05) при більш високому ступені обсіменіння слизової шлунка гелікобактерною  інфекцією, на 41,1% більше було виявлено випадків виразкової хвороби дванадцятипалої кишки і на 40,1 % більше було виявлено випадків дискінезії жовчного міхура за гіпотонічним гіпокінетичним типом у порівнянні з аналогічними даними, отриманими у пацієнтів 2-ї групи.          Ключові слова: хронічний неатрофічний гастрит, виразкова хвороба дванадцятипалої кишки, дискінезія жовчного міхура.   Резюме Была проведена сравнительная характеристика данных комплексного обследования двух групп пациентов с хроническим неатрофическим гастритом: 1-я группа - 23 человека по профессии «водитель дальних  рейсов» (перевозка грузов), 2-я группа - 26 человек, работа которых не связана с перемещением на дальние расстояния. Было выяснено, что у пациентов 1-ой группы хронический неатрофический гастрит протекал достоверно (р < 0,05) при более высокой степени обсеменения слизистой желудка  хеликобактерной инфекцией, на 41,1 % больше было выявлено случаев язвенной болезни двенадцатиперстной кишки и на 40,1% больше было выявлено случаев дискинезии жёлчного пузыря по гипотоническому гипокинетическому типу по сравнению с аналогичными данными, полученными у пациентов 2-ой группы.   Ключевые слова: хронический  неатрофический гастрит, язвенная болезнь двенадцатиперстной кишки, дискинезия жёлчного пузыря.